2017
DOI: 10.1002/cpt.742
|View full text |Cite
|
Sign up to set email alerts
|

Primary Human Lung Alveolus‐on‐a‐chip Model of Intravascular Thrombosis for Assessment of Therapeutics

Abstract: Pulmonary thrombosis is a significant cause of patient mortality; however, there are no effective in vitro models of thrombi formation in human lung microvessels that could also assess therapeutics and toxicology of antithrombotic drugs. Here, we show that a microfluidic lung alveolus-on-a-chip lined by human primary alveolar epithelium interfaced with endothelium and cultured under flowing whole blood can be used to perform quantitative analysis of organ-level contributions to inflammation-induced thrombosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
220
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 264 publications
(239 citation statements)
references
References 50 publications
(64 reference statements)
3
220
0
Order By: Relevance
“…Such efforts have principally focused on airway disease models such as a micro-engineered ACB platform for pulmonary edema, 16 pulmonary thrombosis, 20 and a small airway-on-a-chip model for COPD studies 24 . The former study utilizes the same device and alveolar epithelium (i.e., type II A549 cell line) as in Huh et al 23 to investigate barrier integrity as a result of cytotoxicity arising from therapeutics (e.g., chemotherapy), showing that stretching of the epithelium compromises the pulmonary barrier.…”
Section: Microfluidic Platforms Of the Pulmonary Environmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Such efforts have principally focused on airway disease models such as a micro-engineered ACB platform for pulmonary edema, 16 pulmonary thrombosis, 20 and a small airway-on-a-chip model for COPD studies 24 . The former study utilizes the same device and alveolar epithelium (i.e., type II A549 cell line) as in Huh et al 23 to investigate barrier integrity as a result of cytotoxicity arising from therapeutics (e.g., chemotherapy), showing that stretching of the epithelium compromises the pulmonary barrier.…”
Section: Microfluidic Platforms Of the Pulmonary Environmentmentioning
confidence: 99%
“…This is exemplified in the broad range of pulmonary-related research currently explored in vitro with the support of microfluidic platforms (Fig. 5): notable efforts in the above-mentioned areas include amongst other (i) exploring ALI and ACB barrier characteristics, 23 (ii) conducting therapeutic drug screens, 20 (iii) mapping aerosol deposition patterns in airways, 41 (iv) quantifying the dynamics of liquid plug transport, 86 and (v) assessing airway epithelial injury 84 . In further advancing the field to deliver respiratory platforms that meet the complex integration of anatomical, physiological, and biological constraints, microfluidic designs must strive to recreate more faithfully whole-organ functions; a condition that would encourage expanding the breadth (i.e., scaling-up) of microfluidic platforms [e.g., Figs.…”
Section: Microfluidic Platforms Of the Pulmonary Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…3 In utero exposure results in severe developmental abnormalities, resulting in EPA-FDA advisories against eating fish during pregnancy. 4 Recent studies have found that mercury contamination in the environment is much more prevalent than previously thought, 5 hence the need for innovative -binding curli biofilm circuit. The reporter gene in the MerR-based mercury biosensing circuit is replaced with a curli operon encoding the synthesis and export of self-assembling functional amyloids that are able to bind mercury ions.…”
mentioning
confidence: 99%